Testosterone deprivation intensifies cognitive decline in obese male rats via glial hyperactivity, increased oxidative stress, and apoptosis in both hippocampus and cortex - Titikorn Chunchai (2019)
© 2018 Scandinavian Physiological Society. Published by John Wiley & Sons Ltd Aim: The study hypothesized that testosterone deprivation aggravates cognitive decline in obesity through increasing oxidative stress, glial activation, and apoptosis. Methods: Male Wistar rats (n = 24) were fed with either normal-diet (ND) or high-fat diet (HFD) for 24 weeks. At week 13, ND-fed rats and HFD-fed rats were randomly assigned to two subgroups to receive either a sham-operation or bilateral-orchiectomy (ORX). Rats were evaluated for metabolic parameters and cognition at 4, 8, and 12 weeks after the operation. At the end of protocol, the reactive oxygen species (ROS), glial morphology, and cell apoptosis were determined in hippocampus and cortex. Results: Both HFD-fed groups developed obese-insulin resistance, but ND-fed rats did not. HFD-fed rats with sham-operation showed cognitive decline, when compared to ND-fed rats with sham-operation at all time points. At 4- and 8-week after ORX, the cognitive impairment of ND-fed rats and both HFD-fed groups was not different. However, 12-week after ORX, cognitive decline and of glial hyperactivity of HFD-fed rats had the greatest increase among all groups. Hippocampal ROS levels and apoptotic cells in both HFD-fed groups were equally increased, but the cortical ROS levels and apoptotic cells of HFD-fed rats with ORX were the highest ones. Conclusions: These findings suggest that testosterone deprivation aggravates cognitive decline in obesity via increasing oxidative stress, glial activity and apoptosis.